(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2025)
This contribution engages with recent scholarship on technology, environment, Big Data and Artificial Intelligence that have highlighted their manyfold historical, political and conceptual entanglements on a global scale. These include the way technologies over time have contributed to shape the human and natural environment; how they are changing political and scientific representations of the environment and of its transformations; the ecological costs of contemporary capitalism that exploits data and largely relies on digital technologies. Through this survey of texts and theories – mainly advanced by scholars at the Divison of History, Science, Technology and Environment of the Kth Royal Institute of Technology in Stockholm, Sweden – this contribution aims at pointing at the major strands of critical understanding of contemporary digital technologies from a global and ecologist point of view, also in order to highlight some of their theoretical further possible developments.